2019
DOI: 10.1093/insilicoplants/diz012
|View full text |Cite
|
Sign up to set email alerts
|

MARSHAL, a novel tool for virtual phenotyping of maize root system hydraulic architectures

Abstract: Functional-structural root system models combine functional and structural root traits to represent the growth and development of root systems. In general, they are characterized by a large number of growth, architectural and functional root parameters, generating contrasted root systems evolving in a highly non-linear environment (soil, atmosphere), which makes the link between local traits and functioning unclear. On the other end of the root system modelling continuum, macroscopic root system models associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…The continuous red circles stand for the fully suberized endodermis should keep in mind that the experimental procedure is likely to be more accurate, illustrating the usual tradeoff between precision and throughput. Meunier et al (2020) showed that modifying hydraulic properties changes the root system hydraulic architecture and thus affects the whole root system conductance (K rs ). Tuning root hydraulic conductivity functions to match experimental data or test new hypotheses through simulation studies could therefore show the local impact of root anatomy or cell hydraulic properties on the whole root system conductance.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous red circles stand for the fully suberized endodermis should keep in mind that the experimental procedure is likely to be more accurate, illustrating the usual tradeoff between precision and throughput. Meunier et al (2020) showed that modifying hydraulic properties changes the root system hydraulic architecture and thus affects the whole root system conductance (K rs ). Tuning root hydraulic conductivity functions to match experimental data or test new hypotheses through simulation studies could therefore show the local impact of root anatomy or cell hydraulic properties on the whole root system conductance.…”
Section: Discussionmentioning
confidence: 99%
“…In analogy to the electric circuit model, Couvreur et al (2012) introduced a reduction of the 3-dimensional root hydraulic architecture to modular macroscopic equations and parameters operational for land surface and crop models (Baram et al, 2016;Sulis et al, 2019). Such a multiscale approach offers to connect the dots between models and measurable hydraulic and geometrical properties from the cell to the plant scale (Couvreur et al, 2018;Passot et al, 2018;Meunier et al, 2019) thus integrating essential processes and functional-structural properties for large scale models.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, making free-hand root cross-section takes around 10 to 20 minutes. Meunier et al (2020) showed that modifying hydraulic properties changes the root system hydraulic architecture and thus affects the whole root system conductance ( K rs ). Tuning root hydraulic conductivity functions to match experimental data or test new hypotheses through simulation studies could therefore show the local impact of root anatomy or cell hydraulic properties on the whole root conductance.…”
Section: Discussionmentioning
confidence: 99%
“…. However many studies that used functional-structural root model to simulate water uptake use the hydraulic conductivity that have been estimated by Doussan et al (1998) , such as in R-SWMS (Javaux et al, 2008) , OpenSimRoot (Postma et al, 2017) or MARSHAL (Meunier et al, 2020) . Although those estimations were groundbreaking for the community at the time, we now need to be able to quantify root hydraulic conductivities that directly match the data that we want to assess.…”
Section: Of 24mentioning
confidence: 99%
See 1 more Smart Citation